Vagotomy and the risk of mental disorders: A nationwide population‐based study. (12th July 2021) - Bunyoz, Artemis H.; Christensen, Rune H. B.; Orlovska‐Waast, Sonja; Nordentoft, Merete; Mortensen, Preben B.; Petersen, Liselotte V.; Benros, Michael E.
Abstract: Objective: To investigate vagotomy, the severance of the vagus nerve, and its association with mental disorders, as gut‐brain communication partly mediated by the vagus nerve have been suggested as a risk factor. Methods: Nationwide population‐based Danish register study of all individuals alive and living in Denmark during the study period 1977–2016 and who had a hospital contact for ulcer with or without vagotomy. Follow‐up was until any diagnosis of mental disorders requiring hospital contact, emigration, death, or end of follow‐up on December 31, 2016, whichever came first. Data were analyzed using survival analysis and adjusted for sex, age, calendar year, ulcer type, and Charlson comorbidity index score. Results: During the study period, 113, 086 individuals had a hospital contact for ulcer. Of these, 5, 408 were exposed to vagotomy where 375 (6.9%) subsequently developed a mental disorder. Vagotomy overall was not associated with mental disorders (HR: 1.10; 95%CI: 0.99–1.23), compared to individuals with ulcer not exposed to vagotomy. However, truncal vagotomy was associated with an increased HR of 1.22 (95%CI: 1.06–1.41) for mental disorders, whereas highly selective vagotomy was not associated with mental disorders (HR: 0.98; 95%CI: 0.84–1.15). Truncal vagotomy was also associated with higher risk of mental disorders when compared to highly selective vagotomy ( p  = 0.034). Conclusions: Overall, vagotomy did not increase the risk of mental disorders; however, truncal vagotomy specifically was associated with a small risk increase in mental disorders, whereas no association was found for highly selective vagotomy. Thus, the vagus nerve does not seem to have a major impact on the development of mental disorders.